Phylogenetic analysis of recent classical swine fever virus isolates (CSFV) from Karnataka, India - SHIVARAJ, D B; PATIL, S S; RATHNAMMA, D; HEMADRI, D; ISLOOR, S; GEETHA, S; MANJUNATHA REDDY, G B; SHARADA, R; RAHMAN, H (The Indian Journal of Animal Sciences, 2014)
Classical swine fever (CSF) outbreaks are detected throughout the year. Tissue (spleen and lymph nodes) samples (6) collected from 5 classical swine fever outbreaks in different districts of Karnataka state were subjected to virus isolation in PK–15 cells and virus could be recovered from all the 6 samples. Virus isolation was confirmed by reverse transcription-PCR using primers specific to 5’UTR region and sequenced. Alignment of 150 nucleotides of 5’UTR region with that of 33 published sequences available in Genbank, including 22 Indian CSFV sequences was done to get better epidemiological information on classical swine fever virus (CSFV). Based on the phylogenetic analysis, the isolates from Karnataka could be grouped into subgroup 2.2. Phylogenetic tree confirmed that members of 2.2 subgroup show higher divergence among themselves when compared to other cluster within subgroup 1.1. The study also revealed involvement of 2 different isolates in an outbreak. Most of the outbreaks in our study are due to recent introduction of new stocks of pigs from other places. Even though group 1 viruses are predominant in India, the group 2 viruses are also gradually spreading as confirmed by frequent detection/ isolation of group 2 viruses in the recent years. It appears that subgroup 2.2 viruses are gradually replacing the subgroup 1.1 viruses, indicating the changing epidemiological scenario.